The converse of any statement, true or false, is never always true. The only guaranteed true statement is a contrapositive of a true statement. A contrapositive is a statement where the hypothesis and conclusion are switched, and both sides are negated.
Final Answer: no
Answer:
I will use "complete-the-square" approach if thats ok
first 0.5(x - 2)² - 2
second -2(x - 4)² + 8
Given:
The expression: (1 + x)^n
The Binomial Theorem is used to predict the products of a binomial raised to a certain power, n, without multiplying the terms one by one.
The following formula is used:
(a + b)^n = nCk * a^(n-k) * b^k
we have (1 +x)^n,
where a = 1
b = x
let n = 4
First term, k = 1
4C1 = 4
first term: 4*(1^(4-1))*x^1
Therefore, the first term is 4x. Do the same for the next three terms.
2nd term: k =2
3rd term: k = 3
4th term: k = 4
<span />
Answer: n=0
Step-by-step explanation: